ANALISIS EFISIENSI BIAYA DALAM PENYEDIAAN AIR LAUT UNTUK OCEANARIUM KOTA: STUDI KASUS BXSea BINTARO: - - Wiraguna, Sidi Ahyar Wiraguna (Jurnal Teknik Sipil dan Arsitektur, 2024)
This research focuses on assessing how to procure seawater for the BXSea Bintaro Oceanarium, which is located far from natural seawater sources. The two main options analyzed were the purchase of seawater directly from the coast and the creation of artificial seawater. The research method used in this study was conducted through a qualitative, case study approach by combining literature study, field observation, and the researcher's experience as an oceanarium designer, to gain an in-depth understanding of the technical, economic, and environmental aspects associated with both ways of seawater procurement. The results show that the use of native seawater is more economical and environmentally friendly than artificial seawater. Analysis of the initial costs, long-term operational costs, and logistical and environmental implications of both methods showed the superiority of direct seawater procurement. This method is not only efficient in reducing logistical complexity and initial investment, but also has minimal environmental impact. The conclusions of this study confirm that natural seawater procurement is a cheaper option than the use of artificial seawater. Artificial seawater is significantly up to 5.58 times higher than natural seawater. This study makes an important contribution to the literature of seawater resource management in educational and recreational facilities, and underscores the importance of a sustainable approach in oceanarium development.